Effect of experimental gestational diabetes and administration of glibenclamide on mRNA level of NLRP3-inflammasome and distribution of NLRP3+-cells in mesenteric lymph nodes in progeny - Т. М. Prozorova; V. A. Kamyshna; О. М. Kamyshnyi (Zaporozhye State Medical University, 2017)
A number of dysfunctions of congenital and adaptive components of the immune system are observed in progeny of rats with experimental gestational diabetes (EGD). The key link in pathogenesis of EGD and other diseases is the activation of NLRP3-inflammasome. Therefore, it is an attractive target for pharmaceutical effects. Among the numerous inhibitors of the inflammasome, glibenclamide is the most promising drug, which can effectively correct hyperglycemia in pregnant women. The aim of the study was to determine the level of mRNA expression of NLRP3-inflammasome and the distribution of NLRP3+-cells in mesenteric lymph nodes in progeny of rats with experimental gestational diabetes and after administration of glibenclamide to pregnant Wistar rats. Materials and methods. A molecular-genetic study was carried out using polymerase chain reaction with real-time reverse transcription (RT-PCR) of mRNA expression level of the Nlrp3 gene. The distribution of NLRP3+-cells in MLN of experimental animals was investigated by immunofluorescence and immunohistochemical methods. Results. The development of EGD is accompanied by transcriptional induction of the Nlrp3 gene in MLN in descendants, whose mRNA level increased five-fold (p < 0.05) in 1-month and 3-fold (p < 0.05) in 6-month-old animals. The administration of glibenclamide to pregnant rats inhibited the transcription of the Nlrp3 gene only at the age of 1 month (5.3 times, p < 0.05) and did not change it in the older age group. In the progeny of rats with EGD, the density of the NLRP3+-lymphocyte population in the MLN increased, more clearly at early observation times. The intake of glibenclamide reduced the number of NLRP3+-lymphocytes only at the age of 1 month (by 33 %, the cortex plateau), whereas their number in the medullary cords of 6-month-old progeny even increased. Conclusion. The increased mRNA expression of NLRP3-inflammasome and density of NLRP3+-cells in MLN in descendants of rats with EGD indicates activation of pro-inflammatory signaling. Glibenclamide, as an inhibitor of the activation of the NLRP3-inflammasome, demonstrated its effectiveness only at early observation times.